Combination therapy in hypertension according new ESH/ESC guidelines – which one is the best? - Widecka, Krystyna (Przewodnik Lekarza/Guide for GPs, 2008)
Hypertension is a well documented risk factor for cardiovascular disease. Combination therapy with two or more drugs is required in order to reach the currently recommended blood pressure goals in the majority of hypertensive patients, particularly those with a goal of <130/80 mmHg. Further to the potentiation of the antihypertensive effects, benefits of combination therapy include the potential of fewer adverse affects and of improvement of patients’ compliance. The ASCOT-BPLA trial underlines the cardiovascular benefit of ACE inhibitors, specifically perindopril, beyond that provided by BP reduction. It also suggests that the combination of amlodipine plus perindopril may provide broad-spectrum cardiovascular protection, as well as reduce the incidence of new-onset diabetes mellitus and renal impairment, in addition to its efficacy in lowering BP.